Manufacturing Logistics - Xomidov Anvarbek Ahmadjon o’g’li; Negmatov Bekzodbek Baxodir o‘g‘li (Genius Publishing Group, 2022)
Production is one of the main areas of logistics and plays an important role in the company's activities. In this process, it would be advisable to link the exchange of goods between manufacturing enterprises or the exchange between stores of the same enterprise directly with logistics. In this article we will consider Production Logistics - the essence, purpose and essence of the content
Keywords: Production; logistics; transportation; Warehouse